Exploring library and information experiences of Arab students studying in the United States - Stewart, Kristine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper is an exploration of past and present experiences Arab students studying in the United States have encountered while accessing information. How these experiences, both in their home countries and in the US, have influenced their perceptions of information and libraries and personal and professional lives are also discussed. Cette communication se veut une exploration des expériences passées et présentes des étudiants arabes qui étudient aux États-Unis lorsqu’ils accèdent à de l’information. On y discute de comment ces expériences, à la fois dans leur pays d’origine et aux États-Unis, ont influencé leur perception de l’information et des bibliothèques ainsi que leurs vies personnelles et professionnelles.